Composite welds reinforced in volume with lanthanides - Y. S. Usherenko; S. M. Usherenko; A. L. Minkov; A. H. Yazdani‑Cherati (Литьë и металлургия, 2023)
Under the conditions of dynamic impact of high‑speed clusters of powdered micro‑particles on the volume zone of welding between 110G13 and St.10 steel plates, longitudinal strengthening channel elements are formed, and rare earth elements such as lanthanum and cerium are also synthesized.